Design of cold storage as a storage space for animal vaccines at PT. XYZ - Sigit Yulianto; Srihanto; Hariyanto; Bantu Hotsan S; Dwi Yulianto (JTTM : Jurnal Terapan Teknik Mesin, 2024)
A refrigeration system is a system used to cool a room or an industrial product in the food, pharmaceutical, beverage, vegetable, fruit, and other industries to maintain product quality. One of its uses is as storage for various kinds of pharmaceutical needs, including vaccines for both animals and humans. The problem with cold storage is that existing vaccine storage has been in operation for a long time so it is necessary to study whether it is still able to maintain the vaccine storage temperature, namely -80C. The aim of designing cold storage is to maintain a stable vaccine storage temperature. Because vaccines consist of various kinds of microorganisms that are easy to activate. To maintain the quality of the vaccine, cold storage is needed. The research methodology for writing this thesis is to collect design data from one of the vaccine storage industry companies, and literature studies, then analysis of cooling load planning studies, vaccine storage capacity in cold storage measuring 10 x 10 x m 3 meters and determine the power of the cooling machine using a system. standard vapor compression cooler. The results of the analysis of the refrigeration system planning study showed that the indoor vaccine capacity was 30,600 bottles or 2056,701 lbs (822,680 kg), storage temperature -80C, cooling load 308,133 Btu/hr, or 90,283 W, this system uses R 134 A refrigeration. Using refrigerant, power compressor 23.32 kW, or 32 HP, COP 3.9.